Healthcare providers versus patients' understanding of health beliefs and values - Betty Kennedy; Matloob Rehman; William Johnson; Michelle Magee; Robert Leonard; Peter Katzmarzyk (The Beryl Institute, 2017)
This study examined how well healthcare providers perceive and understand their patients' health beliefs and values compared to patients' actual beliefs, and to determine if communication relationships maybe improved as a result of healthcare providers' understanding of their patients' illness from their perspective. A total of 61 participants (7 healthcare providers and 54 patients) were enrolled in the study. Healthcare providers and patients individually completed survey instruments and each participated in a structured focus group. Healthcare provider and patient differences revealed that patients perceived greater meaning of their illness (p = 0.038), and a greater preference for partnership (p = 0.026) compared to providers. The three qualitative themes most important for understanding patients' health beliefs and values as perceived by healthcare providers were education, trust, and culture. Educating patients was perceived as having the greatest impact and also the easiest method to implement to foster providers' understanding, with at least one patient focus group in agreement of same. Likewise, three themes were derived from patients' perspectives as relatively more important in understanding providers' beliefs and values; bidirectional communication, comprehensive treatment, and discipline. Overwhelmingly, bidirectional communication was perceived as a critical factor as having the greatest impact and may also be easiest to implement according to these patients. When patients and healthcare providers listen and communicate with each other, they are likely to develop a shared understanding that may improve future decision making and quality of care patients receive.